Beginning Ruby on Rails E-Commerce From Novice to Professional - Laine, Jarkko; Hellsten, Christian; SpringerLink (Online service) (Berkeley, CA : Apress : Imprint: Apress, 2007)
Beginning Ruby on Rails E-Commerce: From Novice to Professional is the first book of its kind to guide you through producing e-commerce applications with Rails, the stacked web framework taking the world by storm. The book dives right into the process of creating a production-level web application using agile methodologies and test-driven development combined with Rails best practices. You'll take advantage of the latest crop of Rails plug-ins and helpers that will radically improve your programming schedule. You'll also create a real application step-by-step, plus the book is driven by real-world cases throughout. You will begin by learning how to install Rails and quickly create a product catalog interfaced with your choice of database technologies. Then you'll discover how to build modern, Ajax-powered shopping carts and add useful features like customer feedback modules. Next you'll learn how to integrate your application with open source packages like the Ferret full-text search engine, and how to interface with back-end electronic payment systems. You'll also learn how to make your application work flawlessly with existing production systems using web services, and then ultimately deploy and tune your application for production use.
Project Setup and Proof of Concept -- Author Management -- Book Inventory Management -- Book Catalog Browsing -- Shopping Cart Implementation -- Forum Implementation -- Tagging Support -- Security -- Checkout and Order Processing -- Multiple Language Support -- Acceptance Testing -- Application Deployment -- Performance Optimization.
Keywords: Computer programming; Software engineering; Web Development; Software Engineering/Programming and Operating Systems